Flipped learning as a learning method for students of sports coaching education during the COVID-19 pandemic: a systematic literature review - Abdul Alim; Risti Nurfadhila; Wahyu Dwi Yulianto (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
The ongoing COVID-19 pandemic has resulted in the inability to carry out face-to-face lectures in all universities, including courses for sports science students. It results in less than optimal learning outcomes during the pandemic. Since the closing of face-to-face lectures, most universities in Indonesia have used virtual classrooms in the implementation of learning. However, the data shows that lessons in virtual classrooms without appropriate learning methods can result in a learning loss. This literature review study aims to analyze the effectiveness of flipped learning as a learning solution during the pandemic. The technique used in this study was a literature review. A systematic search of literature regarding the implementation of flipped learning during the pandemic, and the obstacles to the teaching and learning process for sports science students during the pandemic, were conducted on the PubMed, Scopus, Google Scholar, and Semantic Scholar databases. The literature analysis used the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method. A total of seven articles were selected for review. The article review results revealed that implementing flipped learning increased students’ motivation, participation, and learning performance. To conclude, flipped learning can be applied to students in sports science to increase their motivation, participation, and learning outcomes.